Risk Factors for Major Pregnancy Complications in Female Cardiothoracic Surgeons - Sadaf Ijaz, Nosheen, Khalid Ali, Noreen Maqbool Bokhari, Riffat Tanvir (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study is to evaluate the prevalence and risk factors of pregnancy problems among female cardiothoracic surgeons to those of women from similar socioeconomic backgrounds. Methods: Total 278 surgeons were presented in this study. Major antenatal pregnancy complications and the number of hours a mother worked while pregnancy were questions asked of surgeons who had delivered at least one live baby. SPSS 22.0 was used to analyze all data. Results: The patients mean age was 33.19±7.29 years and had mean BMI 26.18±10.27 kg/m2. During third trimester majority of the surgeons performed shift >6 overnight calls/mo and 215 (77.3%) cases had >12 h/wk operated hours. Frequency of major antenatal complication was found in 175 (62.9%) cases. Age >35 years (OR: 3.14, 95% CI: 1.18-7.27) and working more than 12 hours per week during the third trimester (OR: 3.47) were both associated with an increased risk of complications during pregnancy. Conclusion: Female cardiothoracic surgeons suffer major complications during pregnancy. Age and working hours during pregnancy raise the risk of complications. Policies that support mother-fetal health and make childbirth simpler are needed to achieve gender equity in the workplace, training, and early careers. Keywords: Complications, Pregnancy, Cardiothoracic Surgeons, Risk Factors